Experimental Investigation of Motion Control of a Closed-Kinematic Chain Robot Manipulator Using Synchronization Sliding Mode Method with Time Delay Estimation - Tu T. C. Duong; Charles C. Nguyen; Thien Duc Tran (Applied Sciences)
Closed-Kinematic Chain Manipulators (CKCM) have gained attention due to their precise Cartesian motion capability through coordinated active joint movements. Furthermore, ensuring synchronization among the joints of CKCMs is critical for reliable operation. An advanced control scheme for CKCMs that combines Nonsingular Fast Terminal Sliding Mode Control (NFTSMC) with Time Delay Estimation (TDE) while utilizing synchronization errors, namely Syn-TDE-NFTSMC, to effectively address joint errors in CKCMs was developed. NFTSMC enables fast convergence through nonlinear terminal sliding while TDE eliminates the need for prior knowledge of the robot’s dynamics, thereby simplifying its implementation and reducing its computational requirements. It is known that the inclusion of TDE reduces about 98% of the computational requirement of control schemes without TDE. The newly developed control scheme was rigorously evaluated using computer simulation and its control performance was compared with that of existing control methods. This paper presents an experimental study where the newly developed control scheme and other existing control schemes were applied to a real CKCM with 2 degrees of freedom (DOF). The experimental results confirm that the control scheme performed much better than other existing control schemes in terms of synchronization and control performance, achieving a reduction in maximum tracking errors of up to 81% as compared to other existing control schemes. The results confirm the efficacy of the newly developed control scheme in enhancing control precision and system stability, making it a promising solution for improving CKCM control strategies in real-world applications.